Preliminary trial on rooting ability of Telosma cordata (burm. f.) merr. (asclepiadaceae) stem cuttings / H. Sarina and M. Muzamil - H., Sarina; Muzamil, M. (2006)
Rooting ability of Telosma cordata or Bunga Tongkin had been investigated. Sixty (60) healthy stem cuttings of about 20 cm each were used in this study. Half of the cuttings were treated with commercial hormone, Jumbofeed® Rooting Rowder S.P. which contains IBA and NAA hormone plus chelated trace elements. These cuttings were planted in media of (a) 100% peatgrow (organic potting soil), (b) mixture of peatgrow and sand (1:1), and (c) mixture of peat grow, soil and sand (3:2:1). The results two weeks after planting showed that many roots formation was obtain with stem cuttings without hormone treatments in all types of the media and the highest rooting ability observed in the medium contains the mixture of peat grow and sand (1:1) with the average of root length is 6.49 ± 1.03 cm. This study showed that commercial rooting powder used is not significantly induced rooting of stem cuttings of T cordata. ANOVA analysis (α. = 0.05) showed there was much difference observed on rooting of stem cuttings with hormone compared to stem cuttings without hormone in all media. In conclusion, the influence of rooting powder on root formation was far less compared to media used. Optimum water and oxygen balance provide by the mixture of peatgrow and sand (1: 1) is important for root formation of T. cordata.